Organic mulch sheet formulation as an effort to help plants adapt to climate change - Aniek Iriany; Mochammad Chanan; Gunomo Djoyowasito (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose This study aimed to discover the precise material composition and thickness (water hyacinth, rice straw, and banana pseudostem) of organic mulch sheet. Methods This current research was conducted by means of a number of treatments with various material compositions and thickness of organic mulch sheet. Several tests were administered such as chemical analyses on organic mulch sheet, tensile strength, and Vilensky test. Result Various compositions of materials resulted in various chemical analyses of organic mulch sheet. Organic mulch with the strongest tensile strength was during the treatment of 60% water hyacinth, 20% rice straw, and 20% banana pseudostem, reaching 3.28 N/m2. The highest sunlight intensity of mulch composition was during the treatment of M4 (50% water hyacinth, 40% rice straw, and 10% banana pseudostem) with no hole and  absorbing. Conclusion The result showed that water hyacinth, rice straw, and banana pseudostem could be used as the materials for organic mulch sheets. They could add organic matters into the soil, have endurance and strength to apply as mulch in crop cultivation, as well as help plants adapt to climate change.